Cognitive Stimulation and Local Cultural Literacy through Mobile Learning in Integrated Islamic Elementary School Students - Rahmi, Sri Nur; Fairuzzabad, Achmad; Gempawan, Fitra Jaya; Maufiroh, Ulil; Fitria, Fitria; Susilawati, Samsul (World Psychology, 2025)
The integration of digital media in education has become essential for enhancing students’ cognitive development and cultural awareness, particularly at the elementary level. However, the use of interactive platforms that simultaneously stimulate cognitive processes and promote local cultural literacy remains limited, especially in Islamic integrated elementary schools. This study aims to develop and evaluate the effectiveness of Lectora Inspire-based learning media in stimulating cognitive abilities and improving local cultural literacy among students at an Islamic Integrated Elementary School (SDIT) in Tanah Datar, Indonesia. Using a research and development approach adapted from the Borg and Gall model, the study was conducted through stages of needs analysis, product development, expert validation, small group trials, and field testing. The results show that the developed media met high validity and practicality standards, with average expert validation scores reaching 3.7 (very good category). A pretest-posttest design applied to 30 students demonstrated significant improvement in students’ understanding of local culture and indicators of cognitive engagement (p < 0.05). The findings suggest that Lectora Inspire can serve as an effective digital tool for integrating cognitive stimulation with culturally relevant content. This study contributes to innovative strategies in Islamic primary education by fostering both cognitive and cultural dimensions.